The relationship of quality performance appraisal experience on job satisfaction and organizational commitment / Fatin Ilani Iskandar - Iskandar, Fatin Ilani (Faculty of Office Management and Technology, 2013)
The purpose of this paper is to examine the relationship between quality performance appraisal experience on job satisfaction and organizational commitment in CTRM Aviation Sdn. Bhd. In order to identify the relationship between quality of performance appraisal experience on job satisfaction and organizational commitment, 55 sets of questionnaire has been distributed to the CTRM Aviation Sdn. Bhd. The research objective of this study to identify the relationship between quality performance appraisal experience and job satisfaction and to identify the relationship between quality performance appraisal experience and organizational commitment.